Test Of The Effectiveness Of Oral Administration Of Red Dragon Fruit (Hylocereus Polyrhizus) In Preventing Dyslipidemia In Male Wistar Rats (Rattus Norvegicus) Given A High High-Cholesterol Diet - Margaretha Elizabeth Rinni Sondakh; Evan Kurniawan; Syamsul Arifin Nasution (International Journal of Health and Pharmaceutical (IJHP), 2024)
Hyperlipidemia can result from obesity, which causes excess fat to build in the tissue under the skin and spread to other organs and tissues. Indonesia has an alarming dyslipidemia rate. Diet and exercise are vital. Hypolipidemia is in red dragon fruit (Hylocereus spp.) The study examined whether oral red dragon fruit extract prevented dyslipidemia in male Wistar rats (Rattus norvegicus) fed a high-cholesterol diet. This research used 24 mice as test animals. The research procedures included acclimation of the test animals, dragon fruit extract, phytochemical tests, preparation of the test animals, treatment with four groups, dyslipidemia parameter checks, histopathological preparations, and observations. Normal tests for total cholesterol, LDL, LSD, and HDL yielded p-values> 0.05. Homogeneity tests with a 5% significance level yielded p values < 0.05. This study's one-way Anova test yields a significance value of 0.000, or <0.05, whereas the post-hoc LSD test yields <0.05. The best red dragon fruit extract dose for lowering total and LDL cholesterol and raising HDL is 120 mg/mL. The phytochemical experiments on red dragon fruit extract (Hylocereus polyrhizus) show promise for improving the lipid profile.